Tantangan Perguruan Tinggi Menuju Persaingan Globalisasi - Rantung, Danny Ivan (JBE (Journal of Business and Economics); Volume 8 No.2, 2009 JBE UNKLAB, 2009)
Higher education as a subsystem of national education has a mission to provide a good education to its student to be part of the community that has the academic and professional ability. They are also trained to have the ability to improve and expand their knowledge, in science technology, an art, and is able to improve the community and richen their national culture- Higher education in Indonesia needs transformation, changes as a whole; not only for improvement or reformation or to increase the fund for education transformation needed not only includes curriculum changes, but instead the system as a whole. The need of human dimension in Indonesia as the product of higher education should contain the following. good moral, possesses, Indonesian identity, mastered technology and art, acts wise, responsible socially, self confident, creative and critical in thinking, discipline and abide the law.